Attachment theory and close relationships (The Guilford Press, 1998)
Part I: Introduction: Attachment in adulthood / Jeffry A. Simpson and W. Steven Rholes. Part II: Measurement issues: Methods of assessing adult attachment: Do they converge? / Kim Bartholomew and Phillip R. Shaver. Self-report measurement of adult attachment: An integrative overview. / Kelly A. Brennan, Catherine L. Clark and Phillip R. Shaver. Adult attachment patterns: A test of the typological model. / R. Chris Fraley and Niels G. Waller. Working models of attachment: A theory-based prototype approach. / Eva C. Klohnen and Oliver P. John. Part III: Affect regulation: The relationship between adult attachment styles and emotional and cognitive reactions to stressful events / Mario Mikulincer and Victor Florian. Attachment orientations, social support, and conflict resolution in close relationships / W. Steven Rholes, Jeffry A. Simpson and Jami Grich Stevens. Adult attachment and relationship-centered anxiety: Responses to physical and emotional distancing / Judith A. Feeney. Part IV: Clinical applications: The role of attachment in therapeutic relationships / Mary Dozier and Christine Tyrrell. Dismissing-avoidance and the defensive organization of emotion, cognition, and behavior / R. Chris Fraley, Keith E. Davis and Phillip R. Shaver. Childhood revisited: The intimate relationships of individuals from divorced and conflict-ridden families / Kate Henry and John G. Holmes. The associations between adult attachment and couple violence: The role of communication patterns and relationship satisfaction / Nigel Roberts and Patricia Noller. Part V: Conceptual and empirical extensions: Evolution, Pair-bonding, and reproductive strategies: A reconceptualization of adult attachment / Lee A. Kirkpatrick. Adult romantic attachment and individual differences in attitudes toward physical contact in the context of adult romantic relationships / Kelly A. Brennan, Shey Wu and Jennifer Loev